PENTINGNYA PENAMBAHAN MUATAN LOKAL PEMBELAJARAN SEJARAH PADA PERATURAN GUBERNUR BANTEN - Somad, Abdul; Suwandana, Endan (Jurnal Kebijakan Pembangunan Daerah, 2022)
This research is based on implementation and obstacles in learning local history of Banten at the high school level in Banten Province. The methodology used is quantitative, qualitative and descriptive approach with two instruments, i.e. questionnaires and interviews. The results showed that almost 73% of high school history teachers have implemented local history lessons. The scope of local history ranges from historical objects/facts found in the locations closest to schools, districts/cities, to the Banten Province area. The most dominant teaching material is the period of the Sultanate of Banten and the period of the independence revolution. The most interesting finding is the national hero from Banten who was just appointed by the government in 2018, namely K.H. Syam'un as the most studied character. The obstacles faced in learning local history are the lack of teaching materials, learning media, and time allocation. The respondents expect the Banten Provincial Government to issue a policy to make local history a Local Content of the 2013 Curriculum.